PEMASARAN DIGITAL DAN ATMOSFER VISUAL INSTAGRAM: ANALISIS PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KULINER - Fitriyadi; Muhammad Akmal; Setio Utomo; Irwansyah; Devi Rusvitawati (Smart Business Journal (SBJ), 2025)
In the increasingly competitive digital landscape, social media has emerged as a strategic platform for shaping consumer purchasing decisions, particularly within the local culinary sector. This study aims to examine the influence of Instagram-based social media marketing and digital visual atmosphere on consumer purchase decisions at Younki’s Pizza & Mocktails in Banjarmasin. Employing a concurrent triangulation mixed methods design, quantitative data were obtained through structured questionnaires distributed to selected consumers, while qualitative data were collected via in-depth interviews and content analysis of the business’s Instagram presence. The findings indicate that both social media marketing and the visual atmosphere exert a significant influence on consumer purchasing decisions, both individually and collectively. Notably, the digital visual atmosphere emerged as the more dominant factor in shaping consumer perceptions and experiences. The qualitative insights further support this, highlighting that visual elements—such as food presentation, interior design as depicted on social media, content authenticity, and the overall digital ambiance—play a crucial role in fostering emotional engagement and purchase intent. This study contributes theoretically by integrating digital marketing strategies and atmospheric perception into the broader framework of consumer behavior. From a practical perspective, it offers valuable implications for local culinary entrepreneurs in crafting more effective, experience-driven digital marketing approaches. The integrative application of both quantitative and qualitative methodologies facilitates a more holistic understanding of the complex dynamics that underlie consumer decision-making in the contemporary social media marketing environment.